Guest Speaker for the Global Learning System GLS Program at the Binus University, Indonesia - Yuhani, Yusof (2022)
Heartiest congratulations to Assoc. Prof. Dr.. Yuhani Yusof for her contributions as Guest Lecturer for the Global Learning System (GLS) Program at Binus University, Indonesia on 6th April 2022.